Therapeutic management of clinical mastitis in a buffalo with herbal paste adjuvant: A case report - Shaikh, Salahuddin Rafiuddin; Siddiqui, Md Ferozoddin Md Fasihuddin; Syed, Abdul Mujeeb (Buffalo Bulletin, 2024)
An old buffalo was referred to the Department of Veterinary Medicine, College of Veterinary and Animal Sciences, Parbhani. The anamnesis of animal was swelling of udder since five days with abnormal milk, inappetence and earlier treated at local veterinary polyclinic with various treatments but still no improvement observed. On clinical examination, animal was having good body condition, dull and slightly depressed behavior, no abnormality in posture and gait, moist muzzle, slightly congested conjunctival mucous membrane, 103.4 °F temperature, respiration rate - 30 breath per minutes, pulse rate - 68 beats per minutes, one ruminal motility per three minutes. The udder was having marked painful swelling and flaked milk was coming out from the three quarters and blood-tinged milk coming out from left hind quarter. Milk was collected from all four quarters and applied diagnostic test MCMT, SCC, EC and pH and found positive for clinical mastitis. The buffalo was treated with inj. Marbofloxacin 10 mg/kg BW I/M as a single-dose along with a topical herbal paste adjuvant containing Aloe vera, turmeric and lime in proper proportion was applied topically on whole udder and all teats. The paste was applied four times a day and repeated for 6 days with fresh preparation. The buffalo responded positively to the herbal paste with early recovery. There were marked improvements in udder health with reduction in swelling with no pain on palpation of udder and change in color and consistency of milk towards normal from third day onwards. In conclusion, a single dose injection of marbofloxacin along with herbal paste adjuvant is safe and efficacious for the treatment and early recovery of mastitis in buffalo.